Under frequency load shedding scheme for islanded distribution system based on mixed integer linear programming / Sohail Sarwar - Sohail , Sarwar (2020)
In recent years, significant climate changes have pivoted the distribution system towards utilization of renewable energy, particularly through distributed generators (DGs). Although DGs offer many benefits, its integration affects the stability of the system, which could lead to blackout, when the grid is disconnected. The system frequency will drop drastically if DG’s generation capacity is less than the total load demand in the network. In order to sustain the system stability, Under Frequency Load Shedding (UFLS) is a commonly used technique to minimize the difference in load demand and power generation. However, existing load shedding techniques are lack in accurate estimation of power imbalance. Conventional load shedding sheds random loads sequentially until the system’s frequency is recovered. Random and sequential selection of loads without priority results in excessive load shedding, which in turn causes frequency overshoot. Thus, a technique yielding an optimal solution for load shedding incorporating load priority is needed. In this regard, this work proposes an efficient load shedding technique for islanded distribution system. This technique utilizes voltage stability index to rank the unstable loads for load shedding. In the proposed technique, polynomial regression is used to establish a function of power imbalance in the form of frequency decay. Mixed Integer Linear Programming (MILP) optimization produces optimal load shedding strategy based on the priority of the loads (i.e., non-critical, semi-critical, and critical) and the load ranking from voltage stability index. The effectiveness of the proposed technique is tested on three test systems, i.e., 28 bus system, which is a part of the Malaysian distribution network, the IEEE 69 bus system, and the IEEE 137 bus system, using PSCAD/EMTDC. Results obtained prove the effectiveness of the proposed technique in stabilizing the system’s frequency without overshoot by disconnecting unstable non-critical loads on priority. Furthermore, results show that the proposed technique is superior compared to other adaptive techniques on the basis it increases sustainability by reducing the load shed amount and avoiding overshoot in system frequency. Also, its performance is not affected by increasing the number of loads for a large-scale system.